The Chlamydia psittaci Inclusion Membrane Protein 0556 Inhibits Human Neutrophils Apoptosis Through PI3K/AKT and NF-κB Signaling Pathways - He, Zhangping; Xiao, Jian; Wang, Jianye; Lu, Simin; Zheng, Kang; Yu, Maoying; Liu, Jie; Wang, Chuan; Ding, Nan; Liang, Mingxing; Wu, Yimou (Frontiers in Immunology, 2021)
Inclusion membrane proteins (Incs) play an important role in the structure and stability of chlamydial inclusion and the interaction between Chlamydia spp. and their hosts. Following Chlamydia infection through the respiratory tract, human polymorphonuclear neutrophils (hPMN) not only act as the primary immune cells reaching the lungs, but also serve as reservoir for Chlamydia. We have previously identified a Chlamydia psittaci (C. psittaci) hypothetical protein, CPSIT_0556, as a medium expressed inclusion membrane protein. However, the role of inclusion membrane protein, CPSIT_0556 in regulating hPMN functions remains unknown. In the present study, we found that CPSIT_0556 could inhibit hPMN apoptosis through the PI3K/Akt and NF-κB signaling pathways by releasing IL-8 and inhibiting the activation of procaspase-3. Up-regulating the expression of anti-apoptotic protein Mcl-1 and down-regulating the expression of pro-apoptotic protein Bax could also inhibit the translocalization of Bax in the cytoplasm into the mitochondria, as well as induce the transfer of p65 NF-κB from the cytoplasm to the nucleus. Overall, our findings demonstrate that CPSIT_0556 could inhibit hPMN apoptosis through PI3K/Akt and NF-κB pathways, and provide new insights towards understanding a better understanding of the molecular pathogenesis and immune escape mechanisms of C. psittaci.